Correction: Formation of drug nanocrystals under nanoconfinement afforded by liposomes. Issue 15 (1st February 2016) - Cipolla, D.; Wu, H.; Salentinig, S.; Boyd, B.; Rades, T.; Vanhecke, D.; Petri-Fink, A.; Rothen-Rutishauser, B.; Eastman, S.; Redelmeier, T.; Gonda, I.; Chan, H. K.
Abstract : Correction for 'Formation of drug nanocrystals under nanoconfinement afforded by liposomes' by D. Cipolla et al., RSC Adv., 2016, 6, 6223–6233.